RINGGIT GUPERMEN, ENCIK DAN CINA KERATON YOGYAKARTA MASA SULTAN HAMENGKU BUWANA V - Supriyanto Supriyanto (Gelar : Jurnal Seni Budaya, 2013)
In Yogyakarta Palace during The Sultan Hamengku Buwono V (1823-1855), there was an interestingphenomenon around the formation of dancers classification of wayang wong as human actorsthat replaced the role of puppets. Giving the name to group dancers above look like giving levelof social stratification by race in the administrative law of foreign residents in the Sultan Palace.The first class is called Ringgit Gupermen, where there is the best dancers. The second calss isEncik Ringgit which is the middle class dancers. While the last class is Ringgit Chinese as anovice dancers. Class consciousness of Wayang wong dancers on such condition, has a dualtendency at the time of Sultan Hamengku Buwono V. On one hand the class is a bureaucraticframework in political mainstream devices, while on the other hand is a frame work class artistic,cultural tendency in the devices. In the pursuit of political tendency, class dancers into structuralbalance, the balance of class dancers into civilization.